Consumption trend and prescription pattern of opioid analgesics in China from 2006 to 2015. Issue 3 (27th January 2018) - Fang, Wentong; Liu, Tingting; Gu, Zhongsheng; Li, Qian; Luo, Can
Abstract : Objectives: To investigate the consumption trend and prescription pattern of opioids in China from 2006 to 2015, and compare the results with those of selected countries and regions, and identify the pain relief level of China. Methods: Nine different opioid drugs were included in our survey, based on the whole population of China. Consumption of each type of opioid was calculated in grams in reports of the Chinese Food and Drug Administration and the International Narcotics Control Board. Then it was converted to the terms of defined daily doses and morphine equivalents. The correlation between consumption of opioids and gross domestic product, human development index and cancer incidence was analysed by Pearson's correlation test. Results: Defined daily doses increased by 7.89% per year since 2006, and reached 91.05 in 2015. Morphine equivalents increased by 10.57% per year since 2006, and reached 7.24 g in 2015. The average defined daily doses and morphine equivalents were 85.44 and 5.70 g respectively in 2006–2015. Annual defined daily doses of China were lower than the global average. Consumption was related to gross domestic product, but not human development index and cancer incidence. Furthermore, defined daily doses varied greatly in countries with similar gross domestic product or the human development index. Strong opioids or non-intravenous opioids always constituted the majority of opioids, and sustained an increasing tendency in consumption. The predominantly prescribed opioids were fentanyl and morphine. Consumption of oxycodone had a tendency to increase, whereas pethidine tended to decrease. Conclusion: Consumption of opioids has shown an increasing tendency and in the meantime the prescription pattern has changed, indicating the progress of pain relief in China, though it remained far lower than the average global level.